Case files. - Toy, Eugene C. (McGraw-Hill, 2012)
Presents 60 real-life cases that illustrated essential concepts in this area ofmedicine. This title provides each case that includes a complete discussion, clinical pearls, references, definitions of key terms, and USMLE-style review questions.